Some comments on a linear programming problem - BOGDAN, Marcel (Studia Universitatis Babeș-Bolyai Mathematica, 2018)
Besides the very known two exits of the Simplex Algorithm we consider two more cases when at least a solution exists and to decide whether or not the solution is unique. This situation occurred in a linear programming problem, on one hand applying the Simplex Algorithm and on the other hand using Matlab command linprog, that led to the case of unbounded solution set and its construction. Some necessary conditions on data are given so that the set of solutions to be boundedless. Mathematics Subject Classification (2010): 90C05.